Ekonometryczna analiza preferencji konsumpcyjnych artykułów żywnościowych według wykształcenia głowy gospodarstwa domowego - Kurzawa, Izabela; Wysocki, Feliks (Econometric Analysis of Consumption Preferences for Food Products According to Education of Head of Household, 2007)
The main goal of that paper was econometric analysis of consumption preferences for food products according to education of head of household. The analysis was based on the GUS micro - economic data concerning individual Polish household budgets. The consumption econometric model was used as a tool in this study. It resulted from the research that consumption preferences for food products were differentiated between household according to education of head of household. Households of persons with lower level of education have preferred basic food products to supplement food of diet.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 569-577